2020
DOI: 10.3390/biomedicines8080243
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GPR120 Receptor in Essential Fatty Acids Metabolism in Schizophrenia

Abstract: A growing body of evidence confirms abnormal fatty acid (FAs) metabolism in the pathophysiology of schizophrenia. Omega-3 polyunsaturated fatty acids (PUFAs) are endogenous ligands of the G protein-coupled receptors, which have anti-inflammatory properties and are a therapeutic target in many diseases. No clinical studies are concerned with the role of the GPR120 signaling pathway in schizophrenia. The aim of the study was to determine the differences in PUFA nutritional status and metabolism between patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Approximately half of SZ patients have a history of drug abuse disorders [3], and nearly all of them smoke [4]. An Omega-3 polyunsaturated fatty acids (PUFAs) dietary imbalance could aggravate its course while also raising the risk of metabolic complications [5]. Despite the availability of effective pharmacological treatments for HC, up to 50% of patients experience poor illness outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of SZ patients have a history of drug abuse disorders [3], and nearly all of them smoke [4]. An Omega-3 polyunsaturated fatty acids (PUFAs) dietary imbalance could aggravate its course while also raising the risk of metabolic complications [5]. Despite the availability of effective pharmacological treatments for HC, up to 50% of patients experience poor illness outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the decreases of phospholipids in SHR animals, and also in NWR animals after receiving psychostimulants (such as AMPH and LSDX) possibly validate the SCZ animal model adopted here. However, the decreased amounts of omega-3 and omega -6 fatty acids in SCZ animal models compared with control NWR strain could point out to possible compensation mechanisms [52].…”
Section: Discussionmentioning
confidence: 99%
“…The action is considered at least partly through the KP. Furthermore, delivery of active agents to the brain through the blood-brain barrier is under extensive research [39]. Other in vitro and in vivo studies showed therapeutic opportunities through elevated levels of KYNA in PD [40][41][42].…”
Section: Discussionmentioning
confidence: 99%